The Bangkok Civilian Internment Camp from 1941 to 1945: Maintaining the Humanitarian Standards in Wartime - Ratchatapattanakul, Nipaporn (Journal of Arts and Thai Studies, 2024)
Objectives: This research aimed to study the operations of the allied civilian internment camps which were set up by the Thai government from December 1941 to August 1945 to indicate how the camps operated to maintain the humanitarian standards in World War II under Thailand’s alliance with Japan. Methods: This research employed a historical research methodology, with a primary focus on the collection and analysis of primary sources from various archives, including the National Archives of Thailand, Archives of Thammasat University, and the online digital archives of the International Committee of the Red Cross. Additionally, the study incorporated personal memoirs of the individuals involved with the Bangkok Civilian Internment Camp. These data were compiled to gain an understanding of the situations occurring during the period under investigation and to provide context for the in-depth analysis of evidence and the formulation of explanations that address the research objectives. Results: The study revealed that the Bangkok Civilian Internment Camp, established by the Thai government in December 1941 and ceased the operation in August 1945, was one of the internment camps which implemented humanitarian measures during the wartime in alignment with its foundational conditions. As a mixed camp housing both civilians and prisoners of war, it led to the coordination with civilian and military agencies, as well as diplomatic agencies of the host countries and international humanitarian organizations. The camp’s operations mainly abided by the principles of the 1929 Geneva Conventions. Through the collaborative efforts of the military officials, the representatives from the foreign ministries of Thailand and Japan, and the delegates from beneficiary countries and international organizations, the camp successfully upheld the international humanitarian standards during wartime as per the norms of that period. Application of this study: The result shows that even though the war affected both soldiers and civilians, the civilian protection and compensation measures lagged behind the military measures. These findings can be used to design the coordination structures between military and civilian entities and those between governments and private sectors, both in Thailand and globally, to quickly deal with and maintain the humanitarian standards among conflicts.